Fatigue management in the preparation of Olympic athletes - Robson-Ansley, P. J.; Gleeson, M.; Ansley, L. (Journal of Sports Sciences, 2009)
Fatigue is often a consequence of physical training and the effective management of fatigue by the coach and athlete is essential in optimizing adaptation and performance. In this paper, we explore a range of practical and contemporary methods of fatigue management for Olympic athletes. We assesses the scientific merit of methods for monitoring fatigue, including self-assessment of training load, self-scored questionnaires, and the usefulness of saliva and blood diagnostic markers for indicating fatigued and under-recovered athletes, effective nutrition and hydration strategies for optimizing recovery and short-term recovery methods. We conclude that well-accepted methods such as sufficient nutrition, hydration, and rest appear to be the most effective strategies for optimizing recovery in Olympic athletes.